"Łotysz [...] całą swą rozkosz zakłada w próżnowaniu na wzór wszystkich niewolników do ciężkich używanych pracy. [...] Na poddanego kmiecia jedyny". "Pamiętniki księdza Jordana" Kazimierza Bujnickiego w perspektywie postkolonialnej - Samborska-Kukuć, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Father Jordan's Memoirs, a novel by the 19th century Polish Inflanty writer Kazimierz Bujnicki, an exemplar of a nobleman’s epic about the Polish province of yore, discloses a number of stereotypes that characterise so-called post-colonial thinking. The text’s linguistic structures and the author’s dominant stance (Polish-centred approach), when seen through the prism of contemporary Eastern Poland discourse, point to depreciating the Latvian influx perceived as Other-inferior as well as hyperbolising the role of the gentry, with its culture and religion as an imposed standard. The modules that the paper is made up of (zoomorphisation, infernalisation and antiesthetisation) point to the frequently inadvertent metaphorising highlighting inferiority, immaturity, immobility, inability to decide in one’s own affairs; these inadequacies are typical of the group of Latvians inhabiting the semi-utopian hamlet as described in the novel. Hence the patemalisation, their way of perceiving the world around them, combined with the duality of perception exerdscd by the catholic Polish landholder, whose natural identity is of a twofold nature (gentc Livonus, natione Polonus), made up of opposing approaches to colonisation (domination of Latvians, submission toward Russians) and a manifold approach to the multicultural specificity of the Inflanty.